2012
DOI: 10.1021/cm302838v
|View full text |Cite
|
Sign up to set email alerts
|

CsHgInS3: a New Quaternary Semiconductor for γ-ray Detection

Abstract: The new layered compound CsHgInS 3 was synthesized using solid state and flux synthesis techniques. The compound is a semiconductor and shows promising properties for X-ray and γray detection. It features a layered structure that crystallizes in the monoclinic space group C2/c with cell parameters: a = 11.2499(7) Å ́, b = 11.2565(6) Å ́, c = 22.146(1) Å ́, β = 97.30(5)°, V = 2781.8(4) Å 3, and Z = 8. CsHgInS 3 is isostructural to Rb 2 Cu 2 Sn 2 S 6 , where the Hg, In, and Cs atoms occupy the Cu, Sn, and Rb sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…20,[38][39][40][41] Hg on the other hand adopts flexible coordination geometry from linear, trigonal planar, tetrahedral and even octahedral, resulting in diverse structure types. 5 have identified Tl 2 Hg 3 Q 4 (Q = S, Se, Te) as promising detector materials using the "dimensional reduction" approach, 10 and TlHg 6 Q 4 Br 5 (Q = S, Se) using the "lattice hybridization" approach. 39 Here we report a new Tl and Hg containing material, the indirect band gap semiconductor TlHgInS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…20,[38][39][40][41] Hg on the other hand adopts flexible coordination geometry from linear, trigonal planar, tetrahedral and even octahedral, resulting in diverse structure types. 5 have identified Tl 2 Hg 3 Q 4 (Q = S, Se, Te) as promising detector materials using the "dimensional reduction" approach, 10 and TlHg 6 Q 4 Br 5 (Q = S, Se) using the "lattice hybridization" approach. 39 Here we report a new Tl and Hg containing material, the indirect band gap semiconductor TlHgInS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, ACd 5 Ga 4 S 12 (A = K, Rb, Cs) compounds adopt a noncentrosymmetric structure and exhibit interesting IR nonlinear optical thermochromic properties from 298 to 10 K. [28] CsHgInS 3 and CsCdInQ 3 (Q = Se, Te) are expected to be new photoconductive compounds as potential materials for hard radiation detection. [29,30] Furthermore, In 4 Pb x Sn y Se 3 is a promising candidate for mid-temperature thermoelectric materials with an excellent figure of merit (ZT) value of 1.4 at 733 K. [31,32] Although many mixed metal multi-chalcogenides have been reported, quaternary examples containing d 10 transition-metal ions such as Cu 1 + and Ag 1 + are rare. [33][34][35] It was reported that Cu I and Ag I ions tend to exhibit highly diversified and flexible coordination numbers with chalcogens.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ACd 5 Ga 4 S 12 (A=K, Rb, Cs) compounds adopt a noncentrosymmetric structure and exhibit interesting IR nonlinear optical thermochromic properties from 298 to 10 K 28. CsHgInS 3 and CsCdInQ 3 (Q=Se, Te) are expected to be new photoconductive compounds as potential materials for hard radiation detection 29. 30 Furthermore, In 4 Pb x Sn y Se 3 is a promising candidate for mid‐temperature thermoelectric materials with an excellent figure of merit ( ZT ) value of 1.4 at 733 K 31.…”
Section: Introductionmentioning
confidence: 99%
“…The basic building units of these compounds are SiP 4 tetrahedra condensed by vertices to T2 supertetrahedra (Figure 2, yellow) according to the Yaghi [ 20 ] notation. By zigzag fusion of these entities, which was sparely observed in related compounds, [ 6,10–11,21–28 ] chains are formed, depicted in turquoise in Figure 2. Further vertex‐edge condensation of these fused T2‐chain motifs – to the best of our knowledge only once observed [ 29 ] – yields in T2 layers, which are propagating in the ab plane, visualized by condensation of the blue T2 chains in Figure 2.…”
Section: Resultsmentioning
confidence: 71%